The in vivo effects of the factor VII-activating protease (FSAP) on neointima formation - Daniel, Jan-Marcus; Justus Liebig University Giessen (My University, 2009)
Factor VII activating protease (FSAP), a novel plasma protease, can activate both Factor VII independently of tissue factor and pro-urokinase plasminogen activator (uPA). The FSAP gene has been linked to vascular diseases in humans, since the Marburg I (MI, G534E) polymorphism is a prominent risk factor for atherosclerosis and stroke. Furthermore, enhanced FSAP staining was detected in instable atherosclerotic plaques. In contrast to wild type (WT)-FSAP, MI-FSAP has lower enzymatic activity and does not inhibit proliferation of vascular smooth muscle cells (VSMC) due to specific cleavage of platelet-derived growth factor (PDGF)-BB in vitro.In this study, the effect of WT- and MI-FSAP on neointima formation was investigated in a mouse model of wire induced injury of the femoral artery. WT-FSAP was locally applied to the denuded artery in different concentrations and was then compared to MI-FSAP, as well as the active site-inhibited Phe-Pro-Arg-chloromethylketone (PPACK)-FSAP, and a buffer control. WT-FSAP attenuated neointima formation in a dose dependent manner and inhibited proliferation of VSMC, as determined by expression of the proliferating cell nuclear antigen. Since MI-FSAP and PPACK-FSAP did not attenuate neointima formation, the effects of FSAP were mainly due to its proteolytic activity. Following in situ zymography, application of WT-FSAP changed the proteolysis balance in the vessel wall by reducing endogenous plasmin activity. Corresponding to this regulation, the neointima in uPA-/- mice was mainly acellular and nearly completely lacked VSMC. Furthermore, FSAP application did not influence the trans-differentiation of bone marrow-derived progenitor cells into VSMC. Indeed, these cells were predominantly identified as macrophages and could no longer be detected in the vascular wall, when the inflammatory response to the vascular injury had calmed down.The inability of MI-FSAP to inhibit VSMC proliferation in vivo explains the observed linkage between the MI-polymorphism and increased cardiovascular risk. Moreover, FSAP is a prominent regulator of the proteolysis balance at sites of tissue remodelling and could thus account for its association with plaque stability. Hence, FSAP is an important regulator of vascular remodelling with high clinical relevance.

Die Faktor VII aktivierende Protease (FSAP) ist ein Plasmaprotein, das sowohl Faktor VII als auch pro-urokinase (pro-uPA) aktiviert. Der Marburg I (MI, G534E) Polymorphismus des FSAP-Gens gilt als bedeutender Risikofaktor für Atherosklerose. FSAP konnte in einer klinischen Studie in instabilen atherosklerotischen Plaques nachgewiesen werden. MI-FSAP zeigte eine reduzierte proteolytische Aktivität und inhibiert im Gegensatz zu Wildtyp (WT)-FSAP nicht die Proliferation von glatten Gefäßmuskelzellen durch eine spezifische Spaltung von Platelet-derived growth factor-BB (PDGF-BB) in vitro.In einem Mausmodel wurde durch Dilatation der A. femoralis eine Neointimaentwicklung induziert. Anschließend wurden verschiedene Konzentrationen von WT-FSAP um die Arterie gegeben, und diese mit MI-FSAP, dem am aktiven Zentrum inhibierten Phe-Pro-Arg-chloromethyketone (PPACK-) FSAP oder einer Kontrolle ohne FSAP verglichen. Die Applikation von WT-FSAP verminderte konzentrationsabhängig die Neoinitmabildung und inhibierte die Proliferation glatter Gefäßmuskelzellen, während MI-FSAP nur einen marginalen und PPACK-FSAP keinen Effekt hatte. Weiterhin konnte in einer in situ Zymographie gezeigt werden, dass die Expression von aktivem uPA im Zeitverlauf nach Dialtation durch Applikation von WT-FSAP herunterreguliert wurde, was ebenfalls die Proliferation und Migration von glatten Gefäßmuskelzellen hemmte. In diesem Zusammenhang zeigte sich auch ein Fehlen von glatten Gefäßmuskelzellen in der Neointima von uPA-/- Mäusen. Weiterhin hatte FSAP keinen Einfluss auf die Trans-differenzierung von aus dem Knochenmark stammenden Progenitorzellen in glatte Gefäßmuskelzellen. Bei diesen Zellen handelte es sich fast ausschließlich um Makrophagen, die langfristig im vaskulären Remodelling nicht mehr nachweisbar waren. In einem in vivo Model zeigte sich eine inhibierende Wirkung von WT-FSAP auf glatte Gefäßmuskelzellen und eine Beeinflussung der perizellulären Proteolyse. Durch die vermehrte Atherosklerose in Trägern des MI-Polymorphismus sowie die Färbung von FSAP insbesondere in instabilen Plaques lassen sich die Ergebnisse direkt auf die klinische Situation übertragen und unterstreichen die Wichtigkeit von FSAP im vaskulären Remodelling.
Die In-vivo Effekte der Faktor VII aktivierenden Protease (FSAP) auf die Neointima Formation
Keywords: Factor VII-activating protease; smooth muscle cells; neointima; ddc:610